Performance of growing pigs subjected to lighting programs in climate-controlled environments - Janice M. C. Barnabé; Héliton Pandorfi; Nicoly F. Gomes; Marco A. C. Holanda; Mônica C. R. Holanda; José L. S. Carvalho Filho (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this research was to evaluate the thermal comfort, physiological responses and performance of pigs in the growth phase, subjected to supplemental lighting programs in air-conditioned environments, in semiarid region of Pernambuco state, Brazil. Twenty-seven pigs (3/4 Duroc, ¼ Pietrain) were subjected to pens with no climate control, pens with forced ventilation and pens with adiabatic evaporative cooling, associated with 12 h of natural light, 12 h of natural light + 4 h of artificial light and 12 h of natural light + 6 h of artificial light. The experimental design was completely randomized, in a 3 x 3 factorial arrangement with three repetitions. Meteorological responses, physiological responses and performance variables of the animals were recorded. The evaporative cooling system attenuated the action of the stressors and ensured adequate thermal conditions for the animals. Respiratory rate and rectal temperature indicated that evaporative cooling ensured the maintenance of homeothermy. Weight gain and feed conversion were positively influenced for the animals exposed to evaporative cooling, but without significant effect of lighting programs.